2009
DOI: 10.3138/cmlr.65.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Variable Omission ofnein Real-Time French Chat: A Corpus-Driven Comparison of Educational and Non-Educational Contexts

Abstract: This article reports on the variable omission of the French negative particle ne (the first marker of verbal negation) in synchronous (i.e., real-time) electronic communication environments. Patterns of variation in a corpus of non-educational chat (i.e., free, public-access Internet chat) are analyzed and compared to data produced by first-, second-, and third-year American university students of French in an educational setting. First-and second-year students retained ne nearly categorically; third-year stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Although several studies have reported on L2 ne use among advanced learners, some of the individual near‐native speaker rates of ne retention in the present study (e.g., A3, A4) are among the very lowest reported in the L2 literature. One of Howard's () advanced learners consistently retained ne at rates less than 10%, and one learner in van Compernolle and Williams () evinced a rate just over 10%. The two “advanced superior” learners in Sanell () retained ne at rates of 18.2% (after 2.5 years in France) and 33.3% (after 1 year in France).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies have reported on L2 ne use among advanced learners, some of the individual near‐native speaker rates of ne retention in the present study (e.g., A3, A4) are among the very lowest reported in the L2 literature. One of Howard's () advanced learners consistently retained ne at rates less than 10%, and one learner in van Compernolle and Williams () evinced a rate just over 10%. The two “advanced superior” learners in Sanell () retained ne at rates of 18.2% (after 2.5 years in France) and 33.3% (after 1 year in France).…”
Section: Discussionmentioning
confidence: 99%
“…Regan () also reported that lexicalized phrases occasioned less ne retention in her L2 participants, but Sax found no significant effect. With respect to type of postverbal negator, one difficulty is that, as van Compernolle and Williams () found, learners may use very few variants other than pas . Rehner and R. Mougeon () had sufficient data to uncover a strong effect for postverbal negator, but the learners patterned in the opposite direction of the NS norm, retaining ne more frequently with pas than with other negators.…”
Section: Variation and L2 Sociolinguistic Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Most learners who begin to approximate native‐speaker patterns of use have participated in study‐abroad programs or have had other opportunities to access native speaker discourse through, for example, Francophone media (Dewaele 2004; Dewaele and Regan 2002; Regan 1995; 1996; 1997; 2004; Rehner and Mougeon 1999; Sax 2003). In our own previous research (van Compernolle and Williams 2009), we reported that one third‐year learner accounted for nearly one half of all tokens of ne deletion. Although he had never participated in a study abroad program, he was dating a young French woman with whom he nearly always spoke French.…”
Section: Introductionmentioning
confidence: 69%
“… For pedagogical models and specific recommendations, the reader is referred to van Compernolle (2009, in press), van Compernolle and Pierozak (2009), and van Compernolle and Williams (2009). …”
mentioning
confidence: 99%